Study on the Optimal Prestress Level of RC Beams Reinforced with SMA Bars. (22nd December 2021) - Yang, Zeying; Cheng, Zhengquan; Wang, Tianmin; Sun, Yinglin; Wang, Chenghe; Qu, Jianbo; Zhang, Da; Li, Qiang
Abstract : In order to study the optimal prestress level of RC (reinforced concrete) beams strengthened by SMA bars, the finite element software ABAQUS was used to numerically simulate the shear performance of RC beams strengthened by SMA bars with different prestress levels. By using the finite element software ABAQUS, the model of RC beams strengthened by SMA bars with different prestressing levels was established. The influence of SMA bars with different prestressing levels on the shear capacity of RC beams was analyzed from the aspects of stress, strain, load, deflection, and maximum bearing capacity, and the failure types and failure processes of RC beams strengthened with different prestressing levels were obtained. Comparing the numerical simulation results with the experimental results, it is found that the error between the finite element simulation results and the experimental results is less than 10%.